2018
DOI: 10.1080/14647273.2018.1449970
|View full text |Cite
|
Sign up to set email alerts
|

Counsellors’ practices in donor sperm treatment

Abstract: When intended parents choose to have donor sperm treatment (DST), this may entail wide-ranging and long-lasting psychosocial implications related to the social parent not having a genetic tie with the child, how to disclose donor-conception and future donor contact. Counselling by qualified professionals is recommended to help intended parents cope with these implications. The objective of this study is to present findings and insights about how counsellors execute their counselling practices. We performed a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 68 publications
(81 reference statements)
0
9
0
Order By: Relevance
“…This is especially important given that a review of research evidence found that psychological intervention is associated with higher pregnancy rates (Frederiksen et al, 2015). However, psychological care is often insufficiently geared towards dealing with the severe and long term emotional impacts, counselling practices vary dramatically across counsellors and clinics (Visser et al, 2018) and take-up of counselling, due to barriers such as the cost of counselling, is poor (Boivin et al, 1999). The NIAC survey in the UK in 1997 (Kerr et al, 1999) found that 71% of respondents reported they would request counselling if it were offered free, but 31% had received counselling and only 12% had been provided with National Health Service (NHS) funded counselling.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially important given that a review of research evidence found that psychological intervention is associated with higher pregnancy rates (Frederiksen et al, 2015). However, psychological care is often insufficiently geared towards dealing with the severe and long term emotional impacts, counselling practices vary dramatically across counsellors and clinics (Visser et al, 2018) and take-up of counselling, due to barriers such as the cost of counselling, is poor (Boivin et al, 1999). The NIAC survey in the UK in 1997 (Kerr et al, 1999) found that 71% of respondents reported they would request counselling if it were offered free, but 31% had received counselling and only 12% had been provided with National Health Service (NHS) funded counselling.…”
Section: Introductionmentioning
confidence: 99%
“…In the Netherlands, counsellors have various backgrounds; some are psychologists, other social workers. They have no specific education or training on DST counselling and base their counselling on their clinical experience and the policy of the clinic (Visser et al, 2018). Dutch clinics follow a national protocol for infertility counselling on 'possible moral contra-indications' during the intake which also applies for intended parents who opt for DST (NVOG, 2010).…”
Section: Dutch Contextmentioning
confidence: 99%
“…Dutch clinics follow a national protocol for infertility counselling on 'possible moral contra-indications' during the intake which also applies for intended parents who opt for DST (NVOG, 2010). This protocol states that screening intended parents is essential in view of the welfare of the future child, but does not offer any guidelines on how to counsel (Visser et al, 2018). For additional information on the practice of Dutch counsellors, see Visser et al (2018).…”
Section: Dutch Contextmentioning
confidence: 99%
See 2 more Smart Citations